1999
DOI: 10.1177/0273475399211007
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning and Customer Needs in the Undergraduate Marketing Research Course

Abstract: Research was conducted among undergraduates in the target market for a marketing research course to find ways of improving the course image, content, and teaching methodology. This study is unique because it applies the principles of marketing research to a course on marketing research, using the class to identify what students want from their marketing research course. Because the research was personally relevant to the students, they were highly motivated in a course that is historically unpopular. Students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 15 publications
(14 reference statements)
0
47
0
1
Order By: Relevance
“…In addition, many teachers carefully weigh the potential effect of new teaching techniques introduction in their students' evaluation (Clarke III et al, 2001). Several educational resources and methods have been analyzed in the literature such as exercises in class, lectures, use of case studies (Davis, Misra& Van Auken, 2000), combination of written and electronic channels (McNeilly&Ranney, 1998), collection and projects research group, teamwork (Bridges, 1999), and the effect of classroom activities on student learning process (Hamer, 2000).Other studies suggest also that a student's favorable attitude concerning the teaching style leads to better outcomes, and that the relationship between the teaching methods and learning styles results in a more effective learning (Dunn et al, 1990).…”
Section: Learning Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many teachers carefully weigh the potential effect of new teaching techniques introduction in their students' evaluation (Clarke III et al, 2001). Several educational resources and methods have been analyzed in the literature such as exercises in class, lectures, use of case studies (Davis, Misra& Van Auken, 2000), combination of written and electronic channels (McNeilly&Ranney, 1998), collection and projects research group, teamwork (Bridges, 1999), and the effect of classroom activities on student learning process (Hamer, 2000).Other studies suggest also that a student's favorable attitude concerning the teaching style leads to better outcomes, and that the relationship between the teaching methods and learning styles results in a more effective learning (Dunn et al, 1990).…”
Section: Learning Resourcesmentioning
confidence: 99%
“…Teachers should leave their isolated position of single agents to also turn themselves into the students' pupils and partners in the teaching process. This requires the use of IT in schools in an integrated and inclusive way, to teach how to use, consume and interact with technology in a critical way (Bridges, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Os autores concluem que, embora a idade não seja um fator relevante, o nível de experiência contribui negativamente para o uso de técnicas de ensino ativo, assim como o fato de o professor ter que assumir um número maior de horas-aula. Afora os métodos de ensino tradicionais, os métodos e recursos que apareceram mais recentemente na literatura são: (1) aprendizagem experiencial (HICKS, 1996;BRIDGES, 1999;PETKUS, 2000;JOHNSTON, 2000, GREMLER et al 2000BOBBITT et al, 2000;AYERS;UNDERWOOD, 2007;WHEELER, 2008;YOUNG, 2010;MILLS, 2010;GRAU;AKIN, 2011;GREENE, 2011;WIESE;SHERMAN, 2011); (2) simulações e jogos como recursos didáticos (BURNS;GENTRY, 1992;TONKS, 2002;SMITH, 2010;LINDSEY;NEELEY, 2010;RUSSELL-BENNETT, 2010); e (3) uso da tecnologia de computadores em métodos de ensino (e-learning, por exemplo) e como recurso didático (o uso do computador em sala de aula utilizado pelo professor, pelo aluno ou por ambos, simultaneamente) (MOON, 1999;EVANS, 2001;FERREL;FERREL, 2002;HANNAFORD et al, 2002;BOBOT, 2010;LEVIN;MARTIN, 2010).…”
Section: O Ensino De Marketing Se Expande Para Muitas Novas Direçõesunclassified
“…Karns (1993) reported that realworld applications in the marketing classroom are positively related to increased stimulation and effort by students. An article by Bridges (1999) offers evidence that students desire a connection to the real world through guest speakers. On the basis of her results, Bridges (1999) recommended using inclass activities and basing the course grade on exams and team projects among other methods.…”
Section: Course Design Factorsmentioning
confidence: 99%